การใช้หลักพรหมวิหาร 4 ในการปฏิบัติการสอนของครูโรงเรียนโคกน้ำเกลี้ยงวิทยาคม ตำบลโพนทอง อำเภอเมือง จังหวัดกาฬสินธุ์ - พระครูวรจิตตานุรักษ์, พระครูวรจิตตานุรักษ์; นาชัยสินธุ์, วิชิต; หัตกันยา, นิสิตตา (วารสาร ศึกษาศาสตร์ มมร, 2020)
บทคัดย่อ วิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาการใช้หลักพรมวิหาร 4  ในการปฏิบัติการสอนของครู โรงเรียนโคกน้ำเกลี้ยงวิทยาคม ตำบลโพนทอง อำเภอเมืองกาฬสินธุ์ จังหวัดกาฬสินธุ์ 2)เพื่อเปรียบเทียบการใช้หลักพรหมวิหาร  4  ในการปฏิบัติการสอนของครู โรงเรียนโคกน้ำเกลี้ยงวิทยาคม ตำบลโพนทอง อำเภอเมืองกาฬสินธุ์ จังหวัดกาฬสินธุ์  ที่มีเพศ  อายุ  ระดับการศึกษาแตกต่างกัน กลุ่มตัวอย่างที่ใช้ในการวิจัยครั้งนี้คือ นักเรียนโรงเรียนโคกน้ำเกลี้ยงวิทยาคม จำนวน 45 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล ได้แก่แบบสอบถาม สถิติที่ใช้ในการวิเคราะห์ข้อมูล ค่าร้อยละ ค่าเฉลี่ย ค่า  T-test  จำแนกตามอายุ   และระดับการศึกษาที่ต่างกัน  ด้วยการทดสอบค่า  F-test  (One Way ANOVA) ผลการวิจัยพบว่า   จำแนกตามเพศ  พบว่า  นักเรียนที่มีเพศต่างกันมีความคิดเห็นต่อการใช้หลักพรมวิหาร 4 ในการปฏิบัติการ สอนของครู โรงเรียนโคกน้ำเกลี้ยงวิทยาคมโดยรวม เพศชายอยู่ในระดับปานกลาง  เพศหญิงอยู่ในระดับปานกลาง เมื่อพิจารณาเพศชายโดยรวมเป็นรายด้าน ด้านเมตตา ด้านกรุณา ด้านมุทิตา  ด้านอุเบกขา เมื่อพิจารณาเพศหญิงโดยรวมเป็นรายด้าน ด้านเมตตา ด้านกรุณา ด้านมุทิตา ด้านอุเบกขา โดยรวมไม่แตกต่างกัน จำแนกตามอายุ พบว่า  นักเรียนในโรงเรียนโคกน้ำเกลี้ยง กลุ่มตัวอย่างที่ตอบแบบสอบถามส่วน ใหญ่ที่มีอายุ 11 ปี จำนวน 20  คน  คิดเป็นร้อยละ 44.4 รองลงมาคือผู้ที่มีอายุ  12 ปี  จำนวน  16 คน  คิดเป็นร้อยละ  35.6รองลงมาคือผู้ที่มีอายุ  10ปี  จำนวน  9 คน  คิดเป็นร้อยละ  20.0 จำแนกตามระดับการศึกษา พบว่า นักเรียนในโรงเรียนโคกน้ำเกลี้ยง กลุ่มตัวอย่างที่ตอบแบบสอบถามส่วนใหญ่มีระดับการศึกษา ชั้นประถมศึกษาปีที่6 จำนวน  18 คน  คิดเป็นร้อยละ  40.0รองลงมาชั้นประถมศึกษาปีที่5 จำนวน  16 คน  คิดเป็นร้อยละ 35.6 รองลงมาชั้นประถมศึกษาปีที่4 จำนวน  11 คน  คิดเป็นร้อยละ 24.4 Abstract The objectives of this research are 1) to study the use of the temple carpet 4 in the teaching of teachers Khok Nam Kliang Witthayakhom School, Phon Thong Subdistrict, Mueang Kalasin District Karasin Province 2) To compare the use of the Brahmavihara 4 principles in the teachings of teachers Khok Nam Kliang Witthayakhom School, Phon Thong Subdistrict, Mueang Kalasin District Kalasin province with different gender, age, education level The sample group used in this research is 45 students from Khok Nam Klieng Witthayakhom School, tools for data collection Including questionnaires Statistics used in data analysis were percentage, mean, T-test, classified by age and education level. By testing the F-test (One Way ANOVA) The research found that Classified by gender, it was found that students with different sexes had opinions on the use of the main temple of the temple 4 in the teaching practice of Khok Nam Kliang Witthayakhom Witthayakhom School as a whole. Males are at a moderate level. Female is moderate. When considering male sexuality as a kind of compassionate side, in terms of equanimity, when considering female gender as a whole, the kind of kindness, kindness, side of mind, overall equanimity is not different. Classified by age, found that students in Khok Nam Kliang School The sample group that answered the questionnaire Large, aged 11 years, 20 people, representing 44.4 percent, followed by those aged 12 years, 16 people, representing a percentage 35.6, followed by those aged 10 years, 9 people, representing 20.0 percent Classified by education level, found that students in Khok Nam Kliang School The sample group that responded to the questionnaire mostly had education level. Grade 6, number 18, representing a percentage 40.0, followed by grade 5, number 16, representing 35.6 percent, followed by grade 4, number 11, representing 24.4 percentnumber 18, representing a percentage 40.0, followed by grade 5, number 16, representing 35.6 percent, followed by grade 4, number 11, representing 24.4 percent